Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pengguna Jasa - Ferdinand Romelus Anigomang; Sefnat Aristarkus Tang; Elia Maruli (Jurnal Ilmiah Wahana Pendidikan, 2023)
Satisfaction of service users, namely feelings of pleasure or disappointment that arise after comparing the performance (results) of the product in question with the expected performance. This study aimed to determine the effect of the dimensions of service quality consisting of physical evidence, reliability, responsiveness, assurance, and empathy on service user satisfaction at the Simfony Kalabahi Hotel. The population in this study were all consumers who use the services of the Simfony Kalabahi hotel in Alor Regency with a sample of 30 people. The method used in this study is quantitative with descriptive statistical analysis and multiple linear regression analysis. The results of this study are that partial physical evidence has a significant effect on user satisfaction as indicated by a significant t-test value of 0.000. Reliability has a significant effect on user satisfaction as indicated by a significant t-test value of 0.015. Responsiveness has a significant effect on user satisfaction as indicated by the significant value of the t-test of 0.016. Assurance has a significant effect on user satisfaction as indicated by a significant t-test value of 0.034, and empathy has a significant effect on user satisfaction as indicated by a significant t-test value of 0.017. Simultaneously physical evidence, reliability, responsiveness, assurance, and empathy affect user satisfaction which is indicated by a significance value of the F test of 0.000